2020
DOI: 10.24059/olj.v24i3.2194
|View full text |Cite
|
Sign up to set email alerts
|

Video-based Feedback on Student Work: An Investigation into the Instructor Experience, Workload, and Student Evaluations

Abstract: This exploratory study critically analyzes instructor perceptions of leaving video feedback and its impact on workload. Using qualitative and quantitative data, it discusses instructor experiences in adding video feedback to written notes in online courses.  Specifically, this study asks if instructors will feel more "connected" in video feedback courses, if instructors will report increased workloads, and if they see an improvement in their performance evaluations in video feedback courses. The results reveal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…Consequently, some higher education institutions hold screenings of films produced by the countries whose students constitute the most widely represented groups in educational institutions. An illustrative example is an event held by the Asian Studies Centre at Michigan State University which took place on 28 November 2017, from 19:00 to 21:00, and consisted of a screening of the 1998 film Ring (Japan…, 2017) as part of the program "Japanese Film and Culture". It should be noted that the horror genre is not fully relevant for the acculturation process but this very example, which, in our opinion, is iconic for Japanese culture, is able to provide some information about socio-cultural norms specific for Japanese students.…”
Section: Resultsmentioning
confidence: 99%
“…Consequently, some higher education institutions hold screenings of films produced by the countries whose students constitute the most widely represented groups in educational institutions. An illustrative example is an event held by the Asian Studies Centre at Michigan State University which took place on 28 November 2017, from 19:00 to 21:00, and consisted of a screening of the 1998 film Ring (Japan…, 2017) as part of the program "Japanese Film and Culture". It should be noted that the horror genre is not fully relevant for the acculturation process but this very example, which, in our opinion, is iconic for Japanese culture, is able to provide some information about socio-cultural norms specific for Japanese students.…”
Section: Resultsmentioning
confidence: 99%
“…This is in accordance with the study carried out by Vukovic, Roberts, and Wright (2013), which stated that an optimal learning environment reduces math anxiety. Another argument from Ketchum, Lafave, Yeats, Phompheng, and Hardy (2020) also reinforces that carefully designed, and interactive videos are capable of directing students to become engaged in the learning process.…”
Section: Q1: How Do You Feel When You Take An Integral Calculus Course?mentioning
confidence: 97%
“…Regardless, feedback is imperative and subsequently researchers have suggested that the use of a combination of both text-based and video-based delivery is known to be more effective in promoting substantive revision and improvement in students' work, especially on written assignments (Grigoryan, 2017a). Additionally, researchers have indicated that video-based feedback may have a larger impact on students' perceptions of their instructor's social presence (Ketchum et al, 2020;Thomas, West, & Borup, 2017;West & Turner, 2016).…”
Section: Feedback Quality and Deliverymentioning
confidence: 99%
“…Although video-based feedback can require greater WiFi bandwidth, Borup et al determined that learners appreciate how well and clear instructors can elaborate and support in video-based feedback. Like text-based feedback, educators can offer video-based feedback that is personalized and supportive while increasing the likelihood of building relationships with learners (Grigoryan, 2017b;Ketchum et al, 2020). This is especially important when shifting to digital, whereby learners and educators no longer have the benefit of face-to-face conversational exchanges.…”
Section: Feedback Quality and Deliverymentioning
confidence: 99%
See 1 more Smart Citation